Interoception, Contemplative Practice, and Health - Norman Farb (Frontiers Research Topics, 2017)
There is an emergent movement of scientists and scholars working on somatic awareness, interoception and embodiment. This work cuts across studies of neurophysiology, somatic anthropology, contemplative practice, and mind-body medicine. Key questions include: How is body awareness cultivated? What role does interoception play for emotion and cognition in healthy adults and children as well as in different psychopathologies? What are the neurophysiological effects of this cultivation in practices such as Yoga, mindfulness meditation, Tai Chi and other embodied contemplative practices? What categories from other traditions might be useful as we explore embodiment? Does the cultivation of body awareness within contemplative practice offer a tool for coping with suffering from conditions, such as pain, addiction, and dysregulated emotion? This emergent field of research into somatic awareness and associated interoceptive processes, however, faces many obstacles. The principle obstacle lies in our 400-year Cartesian tradition that views sensory perception as epiphenomenal to cognition. The segregation of perception and cognition has enabled a broad program of cognitive science research, but may have also prevented researchers from developing paradigms for understanding how interoceptive awareness of sensations from inside the body influences cognition. The cognitive representation of interoceptive signals may play an active role in facilitating therapeutic transformation, e.g. by altering context in which cognitive appraisals of well-being occur. This topic has ramifications into disparate research fields: What is the role of interoceptive awareness in conscious presence? How do we distinguish between adaptive and maladaptive somatic awareness? How do we best measure somatic awareness? What are the consequences of dysregulated somatic/interoceptive awareness on cognition, emotion, and behavior? The complexity of these questions calls for the creative integration of perspectives and findings from related but often disparate research areas including clinical research, neuroscience, cognitive psychology, anthropology, religious/contemplative studies and philosophy.